Pentraxin-3: A Novel Marker for Indicating Liver Fibrosis in Chronic Hepatitis B Patients? - Balin, Şafak Özer; Cabalak, Mehmet; Sağmak Tartar, Ayşe; Kazancı, Ülkü; Telo, Selda; Demirdağ, Kutbeddin; Akbulut, Ayhan (Turkish Journal of Gastroenterology, 2021)
Background/Aims: PTX-3 is an important marker that plays a role in suppressing inflammation and tissue repair. The aim of this study is to investigate the diagnostic and prognostic characteristics of PTX-3 in CHB patients and the relationship between PTX-3 levels and fibrosis. Materials and Methods: A total of 52 CHB patients and 40 healthy subjects were included in the study. All of the CHB patients underwent liver biopsy and were then scored using a Ishak histologic scoring system. Blood samples were collected to evaluate the PTX-3 levels. Results: Of the subjects who participated in the study, 53% were female. PTX-3 levels were determined as 5.63ng/mL in the control group, and as 0.88ng/mL in the CHB patient group. PTX-3 levels were found to be 1.19ng/mL in stage 1, 0.89ng/mL in stage 2, 0.68ng/mL in stage 3 and 0.55ng/mL in stage 4. Of the CHB patients, 44.2% had significant fibrosis, while 55.7% were identified as not having significant fibrosis. PTX-3 values were 0.64 and 1.0ng/mL in patients with and without significant fibrosis, respectively. The cut-off value for PTX-3 in predicting the absence of significant fibrosis was estimated as 0.9ng/mL. Conclusion: CHB patients were found to have lower serum PTX-3 levels compared to the control group, and these levels decreased even further as the fibrosis stage progressed in these patients. In addition, the significant decrease in PTX-3 levels in patients with stage 1 fibrosis compared to the control group shows that PTX-3 can be used as a non-invasive marker for the early detection of fibrosis (p<0.001).